Organization Of Tourist Awareness Groups In The Development Of Bedengan Tourism Park In Kaliasri Village, Kalipare District, Malang Regency - Widyasari, Anisya Yulis; Zulkarnain, Zulkarnain; Rahma, Rezka Arina (Proceedings Series of Educational Studies, 2024)
Community organization is a group of individuals who come together to create a program or activity aimed at bringing about change in their community. When a community is capable of taking action towards positive change, it is considered empowered. This is evident in the case of the community in Kaliasri Village, which has recognized its local potential and managed to turn it into a tourism attraction. To manage this tourism effort, the community of Kaliasri Village established a group known as the "tourism awareness group" to develop the Bedengan Tourist Park in Kaliasri Village. The purpose of this research is to describe the organization of the tourism awareness group, including the challenges and efforts involved. This study employs a qualitative approach with a case study design. Data collection techniques include observation, interviews, and document studies. The collected data is analyzed through data reduction, data presentation, and conclusion drawing. Data validity is ensured through source triangulation and technique triangulation. The findings of this study indicate that the organization of the tourism awareness group involves several stages: 1) setting goals; 2) forming a management structure; 3) determining programs; 4) planning and allocating resources; and 5) evaluating activities. The group faces challenges related to development capital and natural resources. Despite these challenges, the organization of the tourism awareness group has had a positive impact on the economic conditions of the Kaliasri Village community.